2019
DOI: 10.1097/sap.0000000000001703
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Toe Pulp Flap Used in Reconstruction of Distal Dorsal Toe Defect

Abstract: Background When the distal dorsal part of the great toe is injured, especially with exposure of a tendon, bone, or joint, applying a free or local flap is difficult because of the lack of locally available tissue for reconstruction. Management of the distal dorsal part of a great toe soft tissue defect can be challenging for plastic surgeons. Patient and Method An 18-year-old woman presented with an injury to the dorsal aspect of her right great toe cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…This method was first reported by Niranjan et al 3 for great toe defects and has also been used for reconstruction of neuropathic great toe ulcers in diabetics. 4 A variation as a lateral toe pulp flap of the great toe has also been reported by Cheng et al 5 The above case highlights the potential of this flap as a "substitute" of the great toe's nail, since the aesthetic result is significantly more optimal than the other simpler methods of closure, without compromising functionality or a large donor surface. It is also a reminder that local flaps are very useful in the plastic surgeon's workforce and should never be forgotten or underestimated as a simpler and effective reconstructive tool.…”
Section: Discussionsupporting
confidence: 56%
“…This method was first reported by Niranjan et al 3 for great toe defects and has also been used for reconstruction of neuropathic great toe ulcers in diabetics. 4 A variation as a lateral toe pulp flap of the great toe has also been reported by Cheng et al 5 The above case highlights the potential of this flap as a "substitute" of the great toe's nail, since the aesthetic result is significantly more optimal than the other simpler methods of closure, without compromising functionality or a large donor surface. It is also a reminder that local flaps are very useful in the plastic surgeon's workforce and should never be forgotten or underestimated as a simpler and effective reconstructive tool.…”
Section: Discussionsupporting
confidence: 56%
“…Using this technique like the oblique triangular flap (1980, Vankataswami R 5 ) for fingertip reconstruction is common, but its application in toe reconstruction has been rarely reported. Li-Fu Cheng et al 6 have reported the flap for skin defects on the dorsum of the first toe due to trauma, but there are no existing reports of the flap for the apex of toe.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, few studies focus on the toe pulp aps for reconstructing the nail defects. Cheng et al reported a lateral toe pulp ap for repairing the dorsal toe defect [25] . Tashiro et al reported a second-toe lateral hemipulp ap transfer to cover a third-toe pulp defect [26] .…”
Section: Discussionmentioning
confidence: 99%